Escala de polidez infantil: elaboração e validação de um instrumento de medida - Moreira , Isadora Ferreira Primo (2018)
The present dissertation are two scientific articles that have as their theme politeness, which is understood as the set of behaviors: to greet, to say goodbye, to thank, to request please, to request excuse, to praise and to apologize. The first article describes the elaboration procedures and the psychometric parameters of the Child Politeness Scale (EPI) in three versions (children, parents, and teachers) in three stages. In the first stage, the items of the EPI were elaborated, with each version being composed of 14 items, arranged in the form of declarations, answered on a Likert scale. The second stage consisted of a semantic analysis, carried out with eight children, their respective parents and mothers, and three teachers. All statements were considered appropriate and did not change. In the third stage, the evidence of the validity of EPI was sought. A total of 146 children, aged between seven and eleven years old, were evaluated; 136 mothers, 88 fathers and 22 teachers, who answered the corresponding versions of EPI about these children. The exploratory factor analysis of the versions answered by adults (mothers, fathers and teachers) presented two factors with relative stability of the items and with adequate adjustment indexes. The children version also presented two factors, but two items did not have adequate factor load and were excluded of the analysis. The results are compatible with the theoretical model of conventional politeness and moral politeness, characterizing an evidence of validity based on the internal structure of the scale. In addition, the results of the EPI children's version were correlated with the results of the Inventory of Parental Styles (maternal and paternal). There was a positive correlation of mild to moderate intensity between maternal and paternal practices of positive monitoring and moral behavior and politeness; and negative correlation between paternal practices of neglect and physical abuse and politeness. This correlation characterizes evidence of validity based on relationships with external variables. The second article analyzed the reactions of schoolchildren about seven vignettes of impoliteness. The same 146 children from the first study participated in the study, who answered a structured interview composed of four questions for each vignette. The results showed that there was no significant difference in the children's responses, considering age, sex and school (public or private). It was found that most of the students interviewed reacted adequately to situations of impoliteness, expressing appropriate responses to situations illustrated. The responses were qualitatively analyzed and fit into five categories. There was an agglutination in the category called "adequate", with a total of 91.76% of the responses. The second category that received the most answers was "partially adequate" (5.9%), followed respectively by the categories "justifies impurity" (1.22%), "inadequate" (0.97%) and "outside of context "(0.15%). Finally, the majority of schoolchildren interviewed presented empathetic arguments about people who had suffered impolite actions, knowing to identify how the affected person in the vignette felt.